The american composite - Atwell, Cora (My University, 1897)
Introduction: American national life in its complexness and simplicity is the latest form of civilization. It extends over a broad territory and touches widely diverse types of men and interests. European nations have long expected the division of the states into many independent governments and they but slightly understand what it is that holds them together. Rome is history’s great example of a composite nation, but she never developed a nationality. The nations were conquered and merged into the great army of Roman slaves. Their interest in Rome was that of a conquered people. She took from them their national life with all its vitalizing power and gave in return the peace of death. Her countless captives gave to her their learning in art, literature, and the sciences, and she returned no impulse to increase the store. All interests except the purely personal, one of self gratification were killed. Hence the soundless depths of her corruption politically, morally, and socially. It was this which made the wholesale plundering of her provinces prossible and resulted in very nearly moral death for the whole empire.
Citation: Atwell, Cora. The American composite. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: American; Composite; History; Civilization; Morality; Sociology; Anthropology; Theses; Manuscripts (documents)